Investigation of Attachment Styles and Levels of Athletes in Different Branches to Their Coaches - Canan Bastık; Hayrettin Gümüşdağ (Journal of Educational Issues, 2024)
The aim of this study is to examine the attachment styles in the relationships between coach and individual and team sports athlete. Attachment styles are related to how people interact with other people and how they are influenced by their experiences. Attachment styles may vary in stability later in a person’s life. Because of this, it is possible that the attachment styles of athletes, coaches or educators can be influenced by each other in sports environments. Relations between coach-athlete/athlete-coach are very important for the success of the sporting. The universe of the research is composed of athletes and coaches living in Çorum province, and the sample of the research is composed of 179 athletes (99 woman, 89 man) living in Çorum province and selected by random methods. Turkish version of the Attachment Styles Scale developed by Davis and Jowett (2013) and adapted by Zengin (2019), consisting of 19 items and 3 sub-dimensions, was used in the Relationships between the personal information form created by the researchers and the coach-athlete. It was transferred to the SPSS program and made ready for analysis. The Independent Simple T Test and One Way Anova tests were used from the parametric tests.